EDA and EU defence procurement integration - Georgopoulos, Aris (Routledge, 2015)
The chapter reflects upon the ten years since the establishment of the European Defence Agency (EDA) and analyses its role in the process of European integration in the area of defence procurement. The chapter examines the various initiatives undertaken so far by the EDA in the process of Europeanisation of a policy area that has been linked to core functions of the state and for that reason, based upon a decision making process carried out primarily at national level. Contrary to received wisdom that the EDA’s impact and role has been of limited importance – particularly after the advent of the Defence and Security Procurement Directive 2009/81/EC, proposed by the European Commission and adopted by the Council of the EU and the European Parliament – the chapter argues that the EDA’s contribution in the process of European integration in the field of defence procurement has been especially noteworthy. The chapter submits in particular that the EDA played a crucial role in two ways: First, it demystified and rendered more acceptable the deliberation at the EU level of issues pertaining to the design, rules and policies of defence procurement. Second, by doing so it provided additional political “legitimisation” to the European integration process in this area which led to the enactment of the Defence and Security Procurement Directive. Finally the chapter argues that the EDA must continue its important contribution to the European defence procurement integration and identifies the areas that it may do so.